2000
DOI: 10.4049/jimmunol.164.1.452
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Against the First Ig-Like Domain of Human Platelet Endothelial Cell Adhesion Molecule-1 (PECAM-1) That Inhibit PECAM-1-Dependent Homophilic Adhesion Block In Vivo Neutrophil Recruitment

Abstract: Platelet endothelial cell adhesion molecule (PECAM-1), a member of the Ig superfamily, is found on endothelial cells and neutrophils and has been shown to be involved in the migration of leukocytes across the endothelium. Adhesion is mediated, at least in part, through binding interactions involving its first N-terminal Ig-like domain, but it is still unclear which sequences in this domain are required for in vivo function. Therefore, to identify functionally important regions of the first Ig-like domain of PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
121
1
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(126 citation statements)
references
References 36 publications
3
121
1
1
Order By: Relevance
“…This result may seem counterintuitive, given that several reports indicate that PECAM-1 is an important contributor to leukocyte transendothelial migration in vitro (13)(14)(15) and in vivo (16)(17)(18)(19). However, published data show that the requirement for PECAM-1 in the transmigration of leukocytes is not absolute.…”
Section: Discussioncontrasting
confidence: 48%
“…This result may seem counterintuitive, given that several reports indicate that PECAM-1 is an important contributor to leukocyte transendothelial migration in vitro (13)(14)(15) and in vivo (16)(17)(18)(19). However, published data show that the requirement for PECAM-1 in the transmigration of leukocytes is not absolute.…”
Section: Discussioncontrasting
confidence: 48%
“…[2][3][4][5][6] To determine whether PECAM-1-dependent ligand interactions might play a role in the ability of PECAM-1 to promote endothelial filopodia formation, we studied the effects of two functionally distinct antibodies: mAb 37, which blocks heterophilic binding; and mAb 62, which blocks both homophilic and heterophilic bindings. 49 We found that the initial formation of filopodia by HUVEC was suppressed by both antibodies but not by control IgG (Table 1). Given the functional properties of the antibodies (mAb 37 only blocks heterophilic binding) and the fact that these studies were done with non-confluent cells, these data suggest that endothelial cell filopodia formation may be mediated by PECAM-1-dependent heterophilic binding to matrix proteins.…”
Section: Anti-pecam-1 Antibodies Inhibit Filopodia Formation By Huvecmentioning
confidence: 80%
“…PECAM-1 is thought to play an important role in forming and maintaining the contact inhibited state of endothelial cells in culture as monolayer formation is inhibited by antibodies against the external portion of PECAM-1 (Albelda et al, 1990). In vivo, it is believed to mediate transmigration of white blood cells through the endothelium (Vaporciyan et al, 1993;Nakada et al, 2000).…”
Section: Pecam-1mentioning
confidence: 99%